Analytic Solutions of an Iterative Functional Differential Equations Near Regular Points. (23rd May 2013) - Liu, Lingxia
Abstract : The existence of analytic solutions of an iterative functional differential equation is studied when the given functions are all analytic and when the given functions have regular points. By reducing the equation to another functional equation without iteration of the unknown function an existence theorem is established for analytic solutions of the original equation.